Modeling microwave protein-glycoconjugates formulations from protein-starch composites - Alhassan, Martha Wunnam (2014)
A thesis submitted to the Department of Food Science and Technology in partial fulfilment of the requirements for the award of the degree of Master of Philosophy in Food Science and Technology.